VALUE ANALYSIS SERVICES THROUGH PUBLIC RELATIONS IN MARKETING, INTEGRATED MARKETING COMMUNICATIONS, AND IMAGE PERSONAL SATISFACTION TO IMPROVE THE COMMUNITY - Bachtiar Sembiring (Dinasti Publisher, 2020)
The problem in this study is an indication of public dissatisfaction at the performance of West Java Provincial Parliament, it is seen from the aspiration slow implementation of the legislative function is less precise, long aspiration process, and less emotionally satisfying society. The purpose of this study was to investigate and analyze: The influence of public relations in marketing, integrated marketing communications, and personal image together against the value of service. The influence of public relations in the marketing, integrated marketing communication, personal image, and the value of service together to the satisfaction of the people. The method used is the method descriptive survey and explanatory survey method. The type of investigation used is causality, ie the type of research that suggested a causal relationship between the independent variable, in this case, the public relations in the marketing, integrated marketing communications, and image personal to the dependent variable, the value of community service and satisfaction. The unit of analysis of this research is the organization which meant Governmental Organization (NGO). While the unit of observation is the chairman/member of the NGO in West Java as many as 285 people. Managerial implications of this research is public relations in the marketing of which is reflected by the